Traumatic Brachiocephalic Pseudoaneurysm Presenting as Stroke in a Seventeen‐Year‐Old - Kanwar, Manreet (Clin Cardiol, 2009)
We present a 17‐y‐old male who presented to the emergency room with left arm weakness along with slurred speech. On physical examination, he had stable vital signs with left facial weakness suggestive of lower motor neuron seventh nerve palsy. He was also noted to have a small pulsatile mass in the right infraclavicular region. Further questioning revealed that 3 mo earlier he had suffered blunt chest wall trauma during a football game with fracture–dislocation of the right clavicular head, which was managed conservatively. MRI of the brain showed right frontal cortical changes suggestive of infarct versus vasculitis or edema. Chest CT revealed a 2.5‐ to 3‐cm pseudoaneurysm arising from the brachiocephalic artery, with thrombus formation, along with a surrounding 3 × 4.5 cm hematoma. The patient underwent a successful repair of the pseudoaneurysm with no further neurological sequelae. Traumatic pseudoaneurysm with thrombus formation is an extremely rare cause of stroke. It has been reported in association with the carotid artery, but to our knowledge, this is the first reported case with isolated innominate artery pseudoaneurysm. This case highlights the need for a broad differential when evaluating young patients with neurological deficits. Copyright © 2009 Wiley Periodicals, Inc.